Use of the PLIF and LIP methods for definition of non-stationary temperature fields of water droplets; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Volkov R. S. Roman Sergeevich (2017, 2017)
Title screen